Bandwidth enhancement and miniaturization of circular-shaped microstrip antenna based on beleved half-cut structure for MIMO 2x2 application - Teguh Firmansyah; Supriyanto Praptodiyono; Herudin Herudin; Didik Aribowo; Syah Alam; Dian Widi Astuti; Muchamad Yunus (Institute of Advanced Engineering and Science, 2019)
In this paper, circular-shaped microstrip antenna was simulated, fabricated, and measured accordingly. As the novelty, to enhance bandwidth and reduce antenna size, beleved half-cut microstrip structure is proposed. Further, this proposed antenna structure will be applied to multiple input multiple output (MIMO) antenna 2´2. Therefore, this research was investigated conventional circular shape antenna (CCSA), circular shaped beleved antenna (CSBA), and MIMO circular shaped beleved antenna (MIMO-CBSA) as Model 1, Model 2, and Model 3, respectively. An FR4 substrate with er= 4.4, thickness h=1.6 mm, and tan d=0.0265 was used. The simulation has been conducted using Advanced Design System (ADS). The antenna CCSA/CSBA/ MIMO-CBSA achieve 1.831GHz/2.265 GHz/2.256 GHz, -15.13dB/-17.37dB/-17.25 dB, 1.42/1.31/1.33, and 1.474/2.332/2.322 for center frequency, reflection coefficient, VSWR, and bandwidth, respectively. This antenna has a size 63x90 mm and 51.5x90 mm for CCSA (Model 1) and CSBA (Model 2), respectively. After the structure of MIMO 2´2 was applied, the size of antenna MIMO-CBSA (Model 3) became 180 mm x 180 mm with a mutual coupling (S21)=-26.18 dB and mutual coupling (S31)=-26.41 dB. The result showed that proposed antenna CSBA (Model 2) has wider-bandwidth of 58,2% and smaller-size of 18.2%. Furthermore, after CSBA (Model 2) structure was applied to MIMO 2´2 (Model 3) and the MIMO antenna obtain good mutual coupling (<-15dB). Moreover, the measured results are good agreement with the simulated results. In conclusion, all of these advantages make it particularly valuable in multistandard antenna applications design such as GSM950, WCDMA1800, LTE2300, and WLAN2400.